Mainstreaming Microbes across Biomes. (17th June 2020) - Clarke, Laurence J; Jones, Penelope J; Ammitzboll, Hans; Barmuta, Leon A; Breed, Martin F; Chariton, Anthony; Charleston, Michael; Dakwa, Vongai; Dewi, Fera; Eri, Rajaraman; Fountain-Jones, Nicholas M; Freeman, Jules; et al.
Abstract: Bacteria, fungi, and other microorganisms in the environment (i.e., environmental microbiomes) provide vital ecosystem services and affect human health. Despite their importance, public awareness of environmental microbiomes has lagged behind that of human microbiomes. A key problem has been a scarcity of research demonstrating the microbial connections across environmental biomes (e.g., marine, soil) and between environmental and human microbiomes. We show in the present article, through analyses of almost 10, 000 microbiome papers and three global data sets, that there are significant taxonomic similarities in microbial communities across biomes, but very little cross-biome research exists. This disconnect may be hindering advances in microbiome knowledge and translation. In this article, we highlight current and potential applications of environmental microbiome research and the benefits of an interdisciplinary, cross-biome approach. Microbiome scientists need to engage with each other, government, industry, and the public to ensure that research and applications proceed ethically, maximizing the potential benefits to society.